Of Children’s Natural Rights - Marques, Circe Mara; de Lima Pires, Ana Paula (Instituto de Ciencias Antropológicas, Facultad de Filosofía y Letras, UBA, 2022)
This paper addresses children’s natural rights. The study aims to implement a space for children’s playing with nature elements in a public schoolyard for early childhood education at a town in southern Brazil. In terms of methodology, the investigation consists of action research with 17 four- to five-year-old children. During the investigation, children participated in planning, fundraising, construction, and organising a ‘mud kitchen’. Settlement of the space has gained aid from the Municipal Secretary of Education (SMED), families and small local businesspersons. Results showed that children’s relation with nature is cut across by playful experiences with earth and water, as well as adult, family and teacher participation as positive mediators. Key words: Playing; Early childhood education; Nature; Natural rights